2014
DOI: 10.5551/jat.21626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pioglitazone on Macrovascular Events in Patients with Type 2 Diabetes Mellitus at High Risk of Stroke: The PROFIT-J Study

Abstract: Aim: The present study evaluated the effects of pioglitazone treatment on the incidence of primary cardiovascular events in Japanese subjects with type 2 diabetes mellitus at high risk of stroke. Methods: A prospective, multicenter, randomized, open label, comparative study was conducted among diabetic patients recruited from 50 medical institutions nationwide. A total of 522 patients with hypertension and/or dyslipidemia who had one or more silent cerebral infarcts, advanced carotid atherosclerosis or microal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
(25 reference statements)
0
26
0
1
Order By: Relevance
“…Furthermore, pioglitazone significantly attenuated the risk of stroke recurrence in a subgroup analysis from PROactive study populations 22) . We previously reported the effects of pioglitazone on macrovascular events in Japanese patients with type 2 diabetes mellitus at a high risk of stroke (PROFIT-J Study) 23) . However, the effects of pioglitazone for preventing stroke recurrence in patients with IGT or new DM remains unclear.…”
Section: Study Populationmentioning
confidence: 99%
“…Furthermore, pioglitazone significantly attenuated the risk of stroke recurrence in a subgroup analysis from PROactive study populations 22) . We previously reported the effects of pioglitazone on macrovascular events in Japanese patients with type 2 diabetes mellitus at a high risk of stroke (PROFIT-J Study) 23) . However, the effects of pioglitazone for preventing stroke recurrence in patients with IGT or new DM remains unclear.…”
Section: Study Populationmentioning
confidence: 99%
“…The risk of several isolated secondary outcomes was also reduced significantly, as follows: stroke by 47% (p=0.008); recurrent acute coronary syndrome by 37% (p=0.035); and myocardial reinfarction by 28% (p<0.045) 41, 42 . In a meta-analysis of the cardiovascular risk of TZD, unlike rosiglitazone, pioglitazone reduced the risk of all macrovascular events and myocardial infarction in comparison with comparators 43 . The FDA meta-analysis of clinical trials of pioglitazone also demonstrated the beneficial effect of this drug on cardiovascular event reduction 44 .…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…Znatno je smanjen i rizik u više pojedinačnih sekundarnih ishoda: od ponovnog moždanog udara za 47 % (p = 0,008), od ponovnoga akutnog koronarnog sindroma za 37 % (p = 0,035) i od ponovnog infarkta miokarda za 28 % (p < 0,045) 41, 42 . U meta-analizi kardiovaskularnog rizika od TZD-a pioglitazon je, različito i suprotno od rosiglitazona, smanjivao rizik od svih makrovaskularnih događaja i infarkta miokarda, u usporedbi s komparatorima 9, 43 . I FDA metaanaliza kliničkih ispitivanja pioglitazona pokazala je takav pozitivan učinak lijeka na smanjenje kardiovaskularnih događaja 44 .…”
Section: Tijazolidindioniunclassified
“…Saiki et al reported that pioglitazone suppressed the plasma concentrations of angiotensin II, a marker of adipocyte renin-angiotensin system, in patients with type 2 diabetes 31) . Yoshii et al showed that in patients with type 2 diabetes, pioglitazone significantly improved not only glycemic control but also lipid profiles, including serum levels of LDL-cholesterol and high-density lipoprotein (HDL)-cholesterol, while the cumulative incidence of primary cardiovascular events did not differ according to the treatment with or without pioglitazone during the 2-year study period 32) . In the current study, although pioglitazone treatment significantly reduced vascular lipid accumulation and superoxide production induced by angiotensin II, it did not alter the expression of several fatty Recently, the accumulation of both cholesterol and fatty acid has been suggested to be associated with lipotoxicity in pancreatic -cells 38) .…”
Section: Regulation Of Genes Related To Lipid Metabolismmentioning
confidence: 99%